Vertical alveolar ridge augmentation in implant dentistry : a surgical manual - Tolstunov, Len (John Wiley & Sons Inc., 2016)
Vertical Alveolar Ridge Augmentation in Implant Dentistry: A Surgical Manual presents the main methods of vertical ridge augmentation in a clinically focused surgical manual. After an introductory section on the alveolar ridge and requirements for dental implants, sections are devoted to each procedure: guided bone regeneration, sinus lift, distraction osteogenesis, block grafting, and free bone flaps. Also included is a section relating to intraoral soft tissue grafting to ensure acceptable esthetic outcomes, decision algorithm for bone augmentation, and tissue engineering of the alveolar complex. For each procedure, chapters describe the history of the procedure, diagnosis and treatment planning, the different techniques with corresponding case reports, and complications. Bibliography is provided in each chapter for additional learning.- Resumé vydavatel